Análisis de factibilidad para el desarrollo de un sistema web, que permita el seguimiento de las actividades académicas en la Unidad Educativa Caracol - Pincay Monserrate, Ariel de Jesús (2021)
The objective of this study is to carry out a feasibility analysis for the development of a web system, which allows the monitoring of academic activities in the Caracol Educational Unit. It is intended to solve the problems present within the entity, with respect to the handling of the data. To obtain information, field research was used as a methodology, using an interview as a technique. The information obtained allowed us to know some shortcomings, and also helped in the determination of the main functional and non-functional requirements, which should be considered when creating a system.